“The Many Languages of the Avant-Garde”: In conversation with Grzegorz Bral of Teatr Pieśń Kozła (Song of the Goat Theatre) - Sakowska, Aleksandra (Multicultural Shakespeare: Translation, Appropriation and Performance, 2014)
How to theorise and review avant-garde Shakespeare? Which theoretical paradigms should be applied when Shakespearean productions are multicultural and yet come from a specific locale? These and other many questions interrogating the language of performance in global avant-garde Shakespeare productions are put forward to Grzegorz Bral, the director of the Song of the Goat ensemble in the context of their evolving performance of Macbeth (2006/2008) and their Songs of Lear (2012).